Nexus among green entrepreneurship orientation, green ambidexterity innovation, green technological turbulence and green performance: moderated-mediation evidence from malaysian manufacturing SMEs - Hossain, Mohammad Imtiaz; Ong, Tze San; Jamadar, Yasmin; Teh, Boon Heng; Islam, Ariful (Emerald Publishing, 2024)
Purpose: Amidst the challenges of globalisation and rapid technological advancements, small and medium-sized enterprises (SMEs) in the manufacturing sector are increasingly adopting smart manufacturing practices. Manufacturing SMEs in Malaysia encounter difficulties ensuring sustainability performance and maintaining green ambidexterity innovation (GAI), constrained by limited resources and other barriers. However, academic exploration of these challenges remains limited, particularly within the context of Malaysian SMEs. Thus, based on the natural-resource-based view (NRBV), contingency theory (CT) and ambidexterity paradigm, the goal of this study is to examine the influence of green entrepreneurship orientation (GEO) on corporate green performance (CGP) with the mediation of GAI and moderation of green technological turbulence (GTT) in Malaysian manufacturing SMEs. Design/methodology/approach: This study follows a quantitative method, positivism paradigm, cross-sectional time horizon and structured questionnaire survey. In total, 313 validated responses from Malaysian manufacturing SMEs are analysed using partial least squares—structural equation modelling (PLS-SEM). Findings: The empirical results reveal a positive relationship among GEO, GAI and CGP. Moreover, GAI partially mediates between GEO and CGP. However, GTT did not moderate the GEO-CGP and GEO-GAI associations in the Malaysian manufacturing SMEs context. Originality/value: The findings of this research offer significant insights for academia, policymakers, entrepreneurs, manufacturing management and pertinent stakeholders in developing green manufacturing firms concerning the balance of exploitation and exploration endeavours within the context of an uncertain and volatile industry landscape while simultaneously promoting GEO, GTT and CGP.